(3GddeYI aj Md GdchGcH GdSHYIs - (3CMeO Hf ZdGe Gddg Hf CMeO GdTgjQ HGdche GdHQfS TgGH GdOjf CHh GdYHGSs; (3Gdche GdQjTj , CMeO Hf ZdGe Gddg Hf CMeO Hf eMeO, TgGH GdOjf,J (B836 (3g` s
(3ChdgG (B:s
(3GdMeO ddg LYd GdMd TeSkG MQS ef GdcSha s
(3BNQgG (B:s
(3jfJgi HaVd bGd GdeUfa s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B39s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1565s
Keywords: (3GdQjGVjGJs